FAKTOR - FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK DAERAH DI PROPINSI JAWA TENGAH (TAHUN 2008 - 2011) - Syaefur Rizal, 09.05.52.0175; Kartika, Andi (Students Journal of Accounting and Banking, 2013)
This research is a study that examined the factors that affect tax revenue of regional district and city in Central Java province, the local tax revenue is one of the original components of the area which has a very important role in the financing of organizers of local governance and regional development. The purpose of this research is to know the influence of the number of population, the GDP (gross regional domestic product), the number of tourists and the number of electric customers of local tax revenues. Types of data used in this study is secondary data (time series) in 2008-2011, which is obtained from the Dinas Pendapatan dan Pengelolaan Keuangan Aset Daerah (DPPKAD) of Central Java Province, Badan Pusat Statistik (BPS) of Central Java Province, Dinas Kebudayaan dan Pariwisata of Central Java Province dan PT. PLN (Persero) Distribusion of Central Java. This study uses census method and obtain sample size of 140 objects of research 35 districts and cities in Central Java Province. The results show that the population negatively and significantly to local tax revenue while GDP, the number of tourists and the number of electric customers a positive and significant effect of local tax revenues. Keywords: Population, GDP (gross regional domestic product), the number of tourists, the number elctric customers and local taxes Â